2017
DOI: 10.1515/rehab-2015-0076
|View full text |Cite
|
Sign up to set email alerts
|

Effects of abdominal massage on constipation in palliative care patients – a pilot study

Abstract: Introduction: The problem of constipation in Poland concerns 13.4% of the healthy population. In the case of patients treated with opioids, this number increases to 70-90%, which constitutes a serious problem that lowers the patients’ quality of life. The aim of the study was to assess the effects of abdominal massage, which successfully reduces constipation in various diseases, on palliative care patients. Material and methods: The research included 18 patients of a palliative care facility (mean age 78.3 ± 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…These included, for example, studies of healthy populations, and patient populations with progressive diseases but not at a palliative stage. Twenty-two RCTs met the inclusion criteria 1738 (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These included, for example, studies of healthy populations, and patient populations with progressive diseases but not at a palliative stage. Twenty-two RCTs met the inclusion criteria 1738 (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…21 In the 12 trials involving massage, sessions ranged from three 15- to 45-min massages 25,28 to a 15-min massage daily for 8 weeks. 37 All of the studies that described the setting were conducted in the participants’ homes. 24,28,29,38 Interventions were delivered by massage therapists, other than one study that involved nurses, 25 and one that did not describe the interventionist.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the eight trials' intervention arms included all four key components. Four of the eight trials reported 14 Goepfert et al 15 Kyle 16 Lai et al 17 Serfaty et al 18 Soden et al 19 Wilcock et al 20 Wilkinson et al 21 Massage Dadura 2017 23 Downey 2009 22 Jane et al 24 Kolcaba et al 25 Kutner et al 26 Toth et al 27 Wilkie et al 28 Williams et al 29…”
Section: Aromatherapymentioning
confidence: 99%
“…every day). 22 24 , 26 , 28 , 29 Three provided some form of choice including massage location on the body, pressure and choice of oils. 22 , 27 , 29 No trial reported encouraging interaction; two specified no interaction was allowed or encouraged.…”
Section: Massagementioning
confidence: 99%